Model Pembelajaran Berbasis Discovery- Inkuiri dan Kontribusinya Terhadap Penguatan Kualitas Pembelajaran di Sekolah Dasar - Maruslin Sirait (AR-RIAYAH : Jurnal Pendidikan Dasar, 2017)
A convensional teaching models and monotonous that often happen in teaching process needs to behave seriously by the stakeholder that there are in makro and mikro levels, especially for the teacher that in touch directly in teaching process. teachers need to realize that basically the students have learning variation that we cant make it in the same way. Learning models that should be understood by the teachers in doing learning to create a masterpiece learning process that can change learning situation from passive become active and reactive for the students.